Migrations, Ethnified Communities and Alcohol Consumption: From “Ecuadorianized” drinking in Genoa - Gaspari, Marco; Agrela Romero, Belén (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
This paper analyses, from a socio-anthropological perspective, the role of some alcohol consumption patterns associated with masculinity among the Ecuadorian community in Genova, Italy. The practice of alcohol consumption, in homosocial contexts of migration and associated with sporting activities, is (re)signified under cultural parameters instituted as “alcoholic rituality of masculinity”. Moving away from a pathologization approach to consumption and moving into the study of “alcohol cultures”, migration and consumption, we explore the meanings of ecuadorianised drinking in three scenarios of cultural identity as strategies of territorialization.